Bone morphogenetic protein-7 attenuates pancreatic damage under diabetic conditions and prevents progression to diabetic nephropathy via inhibition of ferroptosis - Song, Sang Hyun; Han, Dawool; Park, Kyeonghui; Um, Jo Eun; Kim, Seonghun; Ku, Minhee; Yang, Jaemoon; Yoo, Tae-Hyun; Yook, Jong In; Kim, Nam Hee; Kim, Hyun Sil (Frontiers in Endocrinology, 2023)
Background: Approximately 30% of diabetic patients develop diabetic nephropathy, a representative microvascular complication. Although the etiological mechanism has not yet been fully elucidated, renal tubular damage by hyperglycemia-induced expression of transforming growth factor-β (TGF-β) is known to be involved. Recently, a new type of cell death by iron metabolism called ferroptosis was reported to be involved in kidney damage in animal models of diabetic nephropathy, which could be induced by TGF-β. Bone morphogenetic protein-7 (BMP7) is a well-known antagonist of TGF-β inhibiting TGF-β-induced fibrosis in many organs. Further, BMP7 has been reported to play a role in the regeneration of pancreatic beta cells in diabetic animal models. Methods: We used protein transduction domain (PTD)-fused BMP7 in micelles (mPTD-BMP7) for long-lasting in vivo effects and effective in vitro transduction and secretion. Results: mPTD-BMP7 successfully accelerated the regeneration of diabetic pancreas and impeded progression to diabetic nephropathy. With the administration of mPTD-BMP7, clinical parameters and representative markers of pancreatic damage were alleviated in a mouse model of streptozotocin-induced diabetes. It not only inhibited the downstream genes of TGF-β but also attenuated ferroptosis in the kidney of the diabetic mouse and TGF-β-stimulated rat kidney tubular cells. Conclusion: BMP7 impedes the progression of diabetic nephropathy by inhibiting the canonical TGF-β pathway, attenuating ferroptosis, and helping regenerate diabetic pancreas.